2015
DOI: 10.1128/jcm.01910-14
|View full text |Cite|
|
Sign up to set email alerts
|

Global Multilocus Sequence Typing Analysis of Mycoplasma bovis Isolates Reveals Two Main Population Clusters

Abstract: Mycoplasma bovis is a major bovine pathogen associated with bovine respiratory disease complex and is responsible for substantial economic losses worldwide. M. bovis is also associated with other clinical presentations in cattle, including mastitis, otitis, arthritis, and reproductive disorders. To gain a better understanding of the genetic diversity of this pathogen, a multilocus sequence typing (MLST) scheme was developed and applied to the characterization of 137 M. bovis isolates from diverse geographical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 36 publications
4
73
1
Order By: Relevance
“…MLST analysis showed that isolate 1 was MLST sequence type 36 (ST36) that did not cluster with any of the clonal complexes previously observed (Rosales et al, 2015). Isolates 2 and 3 produced two different STs, ST30 and ST32, respectively, which clustered in the same clonal complex 1.…”
Section: Mlst Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…MLST analysis showed that isolate 1 was MLST sequence type 36 (ST36) that did not cluster with any of the clonal complexes previously observed (Rosales et al, 2015). Isolates 2 and 3 produced two different STs, ST30 and ST32, respectively, which clustered in the same clonal complex 1.…”
Section: Mlst Analysismentioning
confidence: 86%
“…Isolate 2 was derived from the lungs of a 5-month-old pneumonic calf, and isolate 3 was obtained from bovine fetal stomach contents, both originating from England. Multilocus sequence typing (MLST) was also performed on these isolates using the method described by Rosales et al (2015).…”
Section: Isolatesmentioning
confidence: 99%
“…MLST has been used to genotype several species of bacteria, including several Mycoplasma species: Mycoplasma agalactiae, Mycoplasma bovis, and Mycoplasma hyorhinis (30)(31)(32). This study has described the successful development of a novel M. pneumoniae MLST scheme to allow the characterization of clinical isolates.…”
Section: Discussionmentioning
confidence: 99%
“…So far, M. bovis isolates have been characterised in some countries using genotyping tools such as RAPD, multilocus variable number tandem repeat (VNTR) analysis, and multilocus sequence typing (MLST) (2,3,14,15,23,29) and it revealed that M. bovis strains are divided into two major clonal complexes. However, MLST results published by Dudek et al (7) revealed that a Polish strain (not included in this study) did not cluster with any previously described clonal complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the difficulty of effective isolation of mycoplasmas under laboratory conditions, molecular methods are considered to be the most suitable and have recently been generally recommended for diagnosis of mycoplasmal infection (28). The survey of M. bovis spread and studies on its genetic diversity were performed in different parts of the world because M. bovis is well-equipped to generate diversity, and new clones may appear (2,7,23,29).…”
Section: Introductionmentioning
confidence: 99%